The Effect of Using Somatic Auditory Visual Intellectual (SAVI) Method on students’ Achievement in Writing Analytical Exposition Text - Andika, Jefri (The Explora, 2021)
This study deals with the effect of using Somatic Auditory Visual Intellectual (SAVI) method on students’ achievement in writing analytical exposition text. The objective of thestudy is to find out whether SAVI method significantly affects the students’ achievement in writing analytical exposition text or not. This study was conducted by using experimental group and control group. The population of the study was the students of grade XI of SMK Taman siswa Medan in the academic year 2015-2016, where there were 2 classes of XI Administrasi Perkantoran writer taught by applying lecturing method and at XI Administrasi Perkantoran 2 taught by applying SAVI method with the sample by purposive sampling. The data of the study were obtained from the students’ score of writing test. The writer used Pearson Moment Product formula. They were two data used in this study. They were pre-test and post-test. The data were analyzed by applying t-test formula. After analyzing the data, the result of the study showed that tobserved (2,81) was higher than t-table (0,05) (t-observed > t-table) at the level of significance of a = 5% and at the degree of freedom (df) = 0,5. it can be concluded that applying SAVI method significantly affects on the students’ achievement in writing analytical exposition text or in the other words the hypothesis is accepted.